Islam di Filipina - Andi Syahraeni (Jurnal Adabiyah: Humanities and Islamic Studies, 2010)
Moro Nation in Philippine has shown perseverance to stay exist as a Moslem nation. This struggle has shown to the world when the various interests who try to marginalize them. The problem is the unity within the Moro nation itself is not so strong that from this point, the parties who are not happy about his struggle exploit this weakness. Characteristics of top leadership in Philippines which has several times occurred turnover also showed varied solutions in addressing problems in the southern Philippines that the existence of the Moro nation also provide pluctuative atmosphere in its development. Issues that drive Moro Nation in to a corner from the outside world also provides a negative stigma after the existence of violence committed by cadres as alumni of the Southern Philippines fighters, but they should be more careful to peel the real root of the problem. Wallahu A’lam.